Icno-asociaciones de la transición Precámbrico7Cámbrico en el noroeste de Argentina. - Alonso, R.N.; Aceñolaza, F.G. (Journal of Iberian Geology, 2001)
The discovery of numerous ichnogenera and soft-bodies organisms imprints (Asaphoidichnus, Cochlichnus, Didymaulichnus, Dimorphichnus, Diplichnites, Glockeria, Gordia, Helmintoida, Helminthoidichnus, Helminthopsis, Helminthoraphe, Monomorphichnus, Multipodichnus, Neonereites, Nereites, Oldhamia, Paliella, Planolites, Protichnites, Protopaleodyction, Protovigularia, Scolicia, Squamodictyon, Taphrohelminthopsis, Tasmanadia, Tiernavia, Torrowangea and Treptichnus) in the quartzites and slates of Puncoviscana Formation s.l. in several localities of Northwestern Argentina, let us know in better way the characteristics of the basin that formed the Pampean orogen. The ichnological material here shown is demonstrative of the wide biodiversity of these units. All these elements represent in part the evolution of the Upper Precambrian/ Lower Cambrian basins in western Gondwana. The regional distribution of the ichnofauna, and the relative position in the sedimentary sequence, suggest that the differents ichno-associations (Beltanelliformis, Nereites and Oldhamia) should be assigned to differents moments on the Pampean orogen evolution.